Coercive care and human rights; a complex juxtaposition – part 1. (October 2019) - Little, John D
Objective: To explore the clinical implications associated with the United Nations Convention on the Rights of Persons with Disabilities (UN-CRPD), and coercive practice. Conclusions: Both human rights and clinical perspectives are necessary in the management of the mentally ill.